1996
DOI: 10.1007/bf02174388
|View full text |Cite
|
Sign up to set email alerts
|

TheTy1-copia group retrotransposons inVicia species: copy number, sequence heterogeneity and chromosomal localisation

Abstract: We present an in-depth study of the Ty1-copia group of retrotransposons within the plant genus Vicia, which contains species with widely differing genome sizes. We have compared the numbers and sequence heterogeneities of these genetic elements in three diploid Vicia species chosen to represent large (V. faba, 1C = 13.3 pg), medium (V. melanops, 1C = 11.5 pg) and small (V. sativa, 1C = 2.3 pg) genomes within the genus. The copy numbers of the retrotransposons are all high but vary greatly, with V. faba contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
157
3
5

Year Published

1997
1997
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(168 citation statements)
references
References 41 publications
3
157
3
5
Order By: Relevance
“…Despite this, they retain the retrovirus replicative mode of transposition, which enables them to reinfect the nuclear genome in which they reside (Willhelm and Willhelm, 2001). Successive rounds of insertion therefore lead to an increase in retrotransposon copy number, with extremely large numbers of retrotransposons being found in many eukaryotic genomes (Pearce et al, 1996a;SanMiguel et al, 1996;Meyers et al, 2001). …”
Section: Introductionmentioning
confidence: 99%
“…Despite this, they retain the retrovirus replicative mode of transposition, which enables them to reinfect the nuclear genome in which they reside (Willhelm and Willhelm, 2001). Successive rounds of insertion therefore lead to an increase in retrotransposon copy number, with extremely large numbers of retrotransposons being found in many eukaryotic genomes (Pearce et al, 1996a;SanMiguel et al, 1996;Meyers et al, 2001). …”
Section: Introductionmentioning
confidence: 99%
“…The AT-rich isochores L1 and L2 constitute nearly 2 ⁄3 of most mammalian genomes, yet data suggested that most of the genes are found in the most GC-rich fraction of the genome, in the isochore family H3 (Bernardi 1989). More recently, fluorescent in situ hybridization (FISH) has been used to investigate the distribution of repetitive el-ements in plant genomes (Pearce et al 1996;Heslop-Harrison et al 1997). Analysis of the DNA sequence is a more direct approach.…”
mentioning
confidence: 99%
“…Recent studies have indicated that the majority of this reiterated DNA is composed of retroelements, severa1 classes of mobile DNA that transpose through an RNA intermediate (Smyth et al, 1989;Moore et al, 1991;Pearce et al, 1996;SanMiguel et al, 1996;Suoniemi et al, 1996). In maize, a particular class of retroelements with long-terminal repeats (LTRs), the retrovirus-like retrotransposons, is most abundant.…”
mentioning
confidence: 99%